(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Introduction: Time since death is defined as the time which elapsed since death of a person and time of postmortem examination of the body.Estimation of time since death in forensic medicine is a main objective for conducting any medicolegal autopsy. Though the precise time of death cannot be estimated on the basis of autopsy finding alone. study of the other biochemical changes in the body after death may cut short the problem arising in the estimation of time since death.Materials and methods:The present study is a prospective, cross-sectional study. The study was conducted in the Department of Forensic Medicine at Shaheed Hasan Khan Mewati Government Medical College, Nalhar, a tertiary care teaching institution located in Mewat region of Haryana.Result and discussion:The present study consisted a total of 81 subjects, out of which 56 (69.14%) were male and 25 (30.86%) were females. Male dominance was observed in the distribution of cases with male; female ratio of 2.2:1.Conclusion:Keeping in view, the results of the present study regarding estimation of time since death, we concluded that the time since death can be estimated by using changes in the biochemical markers in cerebrospinal fluid. Potassium showed moderate correlation in cerebrospinal fluid. However other analytes as Na+, Cl-, glucose and creatinine showed